2018
DOI: 10.1038/s41598-018-26006-2
|View full text |Cite
|
Sign up to set email alerts
|

A logic-based method to build signaling networks and propose experimental plans

Abstract: With the dramatic increase of the diversity and the sheer quantity of biological data generated, the construction of comprehensive signaling networks that include precise mechanisms cannot be carried out manually anymore. In this context, we propose a logic-based method that allows building large signaling networks automatically. Our method is based on a set of expert rules that make explicit the reasoning made by biologists when interpreting experimental results coming from a wide variety of experiment types.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…While unliganded FSHR can amplify LHCGR signals, LHCGR can inhibit FSHR-dependent cAMP production [ 110 , 112 ]. FSHR also interacts with RTKs including IGF1R and EGFR, which is important for the AKT and ERK1/2 activation required for gonadotropin induced differentiation of GCs [ 62 , 113 , 114 ].…”
Section: Ovarian Responses To Gonadotropinsmentioning
confidence: 99%
“…While unliganded FSHR can amplify LHCGR signals, LHCGR can inhibit FSHR-dependent cAMP production [ 110 , 112 ]. FSHR also interacts with RTKs including IGF1R and EGFR, which is important for the AKT and ERK1/2 activation required for gonadotropin induced differentiation of GCs [ 62 , 113 , 114 ].…”
Section: Ovarian Responses To Gonadotropinsmentioning
confidence: 99%
“…Similarly, action of the epidermal growth factor receptor (EGFR) during granulosa cell differentiation is required for activation of ERK1/2 (15). Interestingly, the interaction between FSHR and EGFR signaling networks was analyzed using an automated, logic-based approach, suggesting that the ERK1/2-pathway may be activated by EGFR-dependent signals via p38 mitogen-activated protein kinases (MAPK) (16). Moreover, this study confirmed that EGFR is trans-activated through FSHR-mediated pathways involving the proto-oncogene tyrosine-protein kinase SRC .…”
Section: Fshr Interaction With Membrane Receptorsmentioning
confidence: 99%
“…Moreover, this study confirmed that EGFR is trans-activated through FSHR-mediated pathways involving the proto-oncogene tyrosine-protein kinase SRC . On the other hand, EGFR signaling network overlaps, at least in part, that of FSHR, contributing to modulation of the ERK1/2, the phosphatidylinositol-4,5-bisphosphate 3-kinases (PI3K)/protein kinase B (AKT), and the Janus kinase (JAK)/signal transducer and activator of transcription protein (STAT) pathways (16).…”
Section: Fshr Interaction With Membrane Receptorsmentioning
confidence: 99%
“…Several groups have developed frameworks for computational design of the optimal set of experiments to identify the mathematical relationship among the signaling inputs, network status, and the developmental outcome, i.e. model selection (Busetto et al, 2013;Apri et al, 2014;Vanlier et al, 2014;Minas et al, 2017;Rougny et al, 2018). Other statistical frameworks aim to design optimal experiments for determining parameter uncertainty in the chosen model (Dehghannasiri et al, 2015;Fan et al, 2015;Imani et al, 2018;Mohsenizadeh et al, 2018).…”
Section: Modelmentioning
confidence: 99%